THE ROLES OF BRAND TRUST AND E-WOM (ELECTRONIC WORD OF MOUTH) ON SHOPEE’S CUSTOMER LOYALTY IN MANADO - Vina Elsje; Joy Elly Tulung; Maria V. J Tielung (Universitas Sam Ratulangi, 2023)
The purpose of this study is to explore the roles of brand and E-WOM on Customer loyalty, Study the case of customers of Shopee in Manado. This research is qualitative research using a case study approach. Primary data was gathered from an in-depth interview of 20 informants that used Shopee with 2 years of minimum use as the sample chosen using purposive. The data was analyzed through qualitative data analysis. The results show that brand trust has an important role in Customer loyalty, especially among Shopee customers in Manado. The indicators of brand trust namely: Perceived quality, Perceived ease-of-use, customer commitment, customer satisfaction, and product quality are the factors of brand trust to keep the customer stay loyal to the Shopee Brand. The findings for E-WOM that using the coding method also has an important role in Shopee customer loyalty which refers to the affirmation of the customers that perceive E-WOM as a reliable, helpful, adequate, and trustworthy non-commercial informational source. This study suggests that Shopee management or online shop owners keep their quality control over products so that the old customer would be easy to retain and there will be lessened critics over the problem of product quality and time prediction on products' arrival. Thus, the overall benefits can be felt by all parties involved. Keywords: brand trust, E-WOM, customer loyalty, perceived quality, repurchase, quality control